2014
DOI: 10.1002/cssc.201301347
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Copper–Zinc–Tin–Selenide (CZTSe) Solar Cells by Electrodeposition

Abstract: Highly efficient copper-zinc-tin-selenide (Cu2ZnSnSe4 ; CZTSe) thin-film solar cells are prepared via the electrodepostion technique. A metallic alloy precursor (CZT) film with a Cu-poor, Zn-rich composition is directly deposited from a single aqueous bath under a constant current, and the precursor film is converted to CZTSe by annealing under a Se atmosphere at temperatures ranging from 400 °C to 600 °C. The crystallization of CZTSe starts at 400 °C and is completed at 500 °C, while crystal growth continues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 23 publications
2
61
0
Order By: Relevance
“…The EQE curves clearly show that the absorption edge moves towards shorter wavelengths (i.e.,l arger bandgap) with increasing Sc ontents. The bandgap energies calculated from the EQE curves (inset of Figure 2a)a re 1.03, 1.07, 1.14, and 1.18 eV for the CZTSSe thin films with Sc ontentso f0 ,1 5, 25, and 31, respectively.T he bandgap energy of the pure CZTSe is consistent with previous www.chemsuschem.org results, [1,7] and the bandgape nergies of CZTSSe thin films are consistentw ith those estimated from the EDS and XRD analyses. This result, again, shows that the bandgape nergy of the CZTSSet hin films can be controlled very precisely through the Scontent in the CZTSSesolid solution.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The EQE curves clearly show that the absorption edge moves towards shorter wavelengths (i.e.,l arger bandgap) with increasing Sc ontents. The bandgap energies calculated from the EQE curves (inset of Figure 2a)a re 1.03, 1.07, 1.14, and 1.18 eV for the CZTSSe thin films with Sc ontentso f0 ,1 5, 25, and 31, respectively.T he bandgap energy of the pure CZTSe is consistent with previous www.chemsuschem.org results, [1,7] and the bandgape nergies of CZTSSe thin films are consistentw ith those estimated from the EDS and XRD analyses. This result, again, shows that the bandgape nergy of the CZTSSet hin films can be controlled very precisely through the Scontent in the CZTSSesolid solution.…”
supporting
confidence: 88%
“…[7] The electrochemical deposition was performed using at wo-electrode system with aM o-coated soda-lime glass substrate (3 4 cm 2 ,w orking electrode) and aP tp late (counter electrode). The films were deposited at ac onstant current density of À1.18 mA cm À2 for 1200 s. Before the deposition, the substrates were cleaned with acetone, ethanol, and deionized water followed by drying in an itrogen stream.…”
Section: Experimental Section Sample Preparationmentioning
confidence: 99%
“…Two of the most important parameters to prepare CZTS are sulfurization time and annealing temperature. Before annealing, a drying step is carried out at 200–300 °C to maximize solvent evaporation8. However, some reports indicate that intermediates like binary sulfide of the constituent elements, bimetallic alloys or ternary Cu x SnS y can form at these temperatures9.…”
mentioning
confidence: 99%
“…Lee et al reported that CZTS thin-film solar cells could achieve a 2% conversion efficiency [19] when soaked in an aqueous KCN solution, and we had improved the efficiency to higher than 5%. We use the same process with the CZTS samples, and very recently, we had achieved a conversion efficiency of 8% for CZTSe solar cells by applying selenization via KCN etching [20].…”
Section: Methodsmentioning
confidence: 98%